Compatibility of Western and Islamic Models of Democracy A Comparative Analysis - Šrámek, Ondřej (2009)
The thesis looks at compatibility of Islam and democracy in a new way. The main method is analysis of political ideologies. A number of models of democracy are identified in both the Western and Islamic context. These are then originally compared in a framework of classification by the source of political sovereignty and political action.